Signicef® (levoflaxacin 0.5%) eye drops in clinical practice - E. A. Spiridonov (Oftalʹmologiâ)
Purpose: to evaluate the effect of levoflaxacin 0.5% eye drops/Signicef® (Promed Exports, India) for prevention of infectious complications following ocular traumas and intraocular surgery as well as infectious disorders treatment.Methods: In retrospective analysis were included 102 cases of different ophthalmic pathologies following intraocular surgery, i.e., phacoemulsification (27 cases), extracapsular cataract extraction (40 cases), intravitreal injection/IVt of Lucentis (23 cases), abscess/phlegmon drainage (3 cases). Levofloxacin 0.5% (Signicef® Eye Drops) was prescribed according to a scheme before and following ocular surgery for prevention and treatment of infectious complications.Results: No infectious complications following eye surgery or IVt were observed.Conclusion: Signicef® use as antibacterial mono-medication is reasonable and sufficient for prevention of post-op infectiouscomplications as well as ocular traumas and infectious corneal disorders treatment.